1973
DOI: 10.1073/pnas.70.12.3311
|View full text |Cite
|
Sign up to set email alerts
|

“Private” Genetic Variants and the Frequency of Mutation Among South American Indians

Abstract: Electrophoretic studies were performed on 15 proteins of blood serum and of erythrocytes, from blood specimens from 72 villages of six relatively unacculturated and genetically pure Indian tribes of South America, for a total of 56,237 determinations. At least 10 different "private" variants were encountered, in 131 people. Two previously recognized genetic polymorphisms of these 15 proteins were also encountered. On the assumption that these variants are neutral from the standpoint of natural selection, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
2

Year Published

1981
1981
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(30 citation statements)
references
References 17 publications
0
28
0
2
Order By: Relevance
“…The number of effective migrants (Nm) was estimated by three different methods: the Slatkin private alleles method 47 (namely, alleles found in only one population as referred to by Neel 48 ), and by F-and R-statistics of each locus according 42 and Hartl and Clark 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…The number of effective migrants (Nm) was estimated by three different methods: the Slatkin private alleles method 47 (namely, alleles found in only one population as referred to by Neel 48 ), and by F-and R-statistics of each locus according 42 and Hartl and Clark 50 ).…”
Section: Methodsmentioning
confidence: 99%
“…However these stochastic models fail to justify the high levels of average heterozygosity in Troglophilus unless a value of IJ-= 10-4 is assumed. We consider this mutation rate unrealistically high for average values even if single loci have been detected in man with mutation rates of a comparable order of magnitude (Neel, 1973).…”
Section: Determinants Of Genetic Variabilitymentioning
confidence: 99%
“…where K is the average number of rare variants per locus, N is population size and t is the average existing time of a mutant [7,9] . Kimura and Ohta [8] also showed that 4 log , 1 e e p t p N p p ¬ ® (2) in which N e is the effective population size and p is the frequency of the mutant allele.…”
Section: Introductionmentioning
confidence: 99%